Métodos computacionais de Monte Carlo para determinar do zeros de Fisher no modelo de Heisenberg anisotrópico 2D - Gabriel Bruno Garcia de Souza (2021)
In this work we studied the phase transitions that chatacterize the Anisotropic heisenberg spin model varying the anisotropy parameter δ. In this work we used Monte Carlo Methods to run simulations of the model and used a "reweighting" method based on the energy histograms combined with a method based on the partial knowledge of the Fisher Zeros that allow the determination of the dominant zero with precision. The method used in this work was sufficient to determinate the critical exponents that describes the phase transitions and allowed us to obtain the critical temperatures for many values of δ. The model shows an Order-Disorder phase transition for δ > 1 that belongs to the 2D Ising universality class. The main focus was to study the model for δ ←− 1−. Any phase transition at the isotropic limit δ = 0, was detected.